Radiation-induced damage to concrete biological shielding materials: a state-of-the-art review - Ahmad, Nasuha; Idris, Mohd Idzat; Amran, Mugahed; Hussin, Azimah; Abdul Karim, Julia; Masenwat, Norazreen; Rashid, Raizal S. M.; Yahya, Mohd Syukri (National University of Malaysia, 2025)
Concrete is the primary material for such shielding due to its mechanical and structural properties, suitable for neutron and gamma radiation protection. This review provides a comprehensive examination of the impact of nuclear irradiation on the structural integrity of concrete used in biological shielding within nuclear power plants (NPPs). This review highlights the critical role of the hydrogen content of concrete in attenuating neutron flux and its versatility in shape, density, and cost-eff ectiveness. The review was systematically collected and reviewed previous research papers on the topic, focusing on studies that address the degradation of mechanical properties in concrete exposed to gamma and neutron radiation. Our methodology involved an extensive literature search, critical analysis, and synthesis of fi ndings from peer-reviewed journals, conference proceedings, and technical reports that specifically address the degradation of mechanical properties in concrete structures exposed to gamma and neutron radiation. Gamma radiation induces radiolysis in hydrated cement paste, while neutron radiation causes alterations in the crystalline structure of aggregates, leading to volumetric expansion and reduced mechanical strength. Additionally, this review highlights the combined effects of chemical attacks, moisture, and elevated temperatures on concrete degradation during reactor operation. The key findings underscore the need for further research into the degradation mechanisms of concrete biological shielding, emphasizing the influence of various types of nuclear radiation. This understanding is crucial for ensuring concrete’s long-term durability and effectiveness in NPPs, thereby contributing to the safe and sustainable operation of nuclear energy facilities.